Superconducting properties of YBaCuO thin films obtained by thermocycling - Yugay, K. N.; Skutin, A. A.; Yugay, K. K.; Seropjan, G. M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1997)
YBaCuO films fabricated by laser ablation method were subjected to a thermocycling. Our investigations showed that the degradation process of the current transport properties of films is accompanied by the appearance of a maximum on the curve of the critical current density, depending on the number of thermocycles. This effect manifests itself most strongly in the films with degraded superconducting properties. The critical temperature and the transition width vary only slightly in this case.